Overview of Provisions for Import of Medical Devices into India under Central Licensing Approval Authority (CLAA) Scheme and Medical Device Rules, 2017 - Sethi, Rohin; Popli, Harvinder (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2017)
Background: The Government of India regulates medical devices through a specialized division called, Medical Device and Diagnostics Division, CDSCO, Min of Health and Family Welfare. Earlier, only 14 categories of Medical Devices, called Notified Devices were regulated under CLAA scheme for the purpose Manufacture, Import, Sale and Distribution. On 17th October 2016, a draft of rules, called Medical Device Rules, was published by Ministry of Health and Family Welfare, in Official Gazette, for feedback from industry. Objective: In this paper we would examine the provisions for import of Medical Devices under CLAA scheme and Medical Device Rules, 2017 and make easier to grasp the regulatory system of India for any manufacturer who wishes to enter Indian Market. Discussion: After due consideration, the Medical Device Rules, 2017 were passed and set for implementation by 1st January 2018. This will create a separate registration and oversight system for drugs and medical devices. Drug Controller General of India would remain the Licensing Authority for Import of devices under the new system. Indian Medical Device Industry is primarily import oriented. Indian Market presently offers tremendous opportunities for high-end sophisticated device manufacturers as most of the high end innovative products are imported into the country. The import of medical devices for the year 2016, stood at 208,230.65 million.
Keywords: DCGI